L-carnitine prevents lenvatinib-induced muscle toxicity without impairment of the anti-angiogenic efficacy - Jing, Zheng; Iba, Tomohiro; Naito, Hisamichi; Xu, Pingping; Morishige, Jun-ichi; Nagata, Naoto; Okubo, Hironao; Ando, Hitoshi (Frontiers in Pharmacology, 2023)
Lenvatinib is an oral tyrosine kinase inhibitor that acts on multiple receptors involved in angiogenesis. Lenvatinib is a standard agent for the treatment of several types of advanced cancers; however, it frequently causes muscle¬-related adverse reactions. Our previous study revealed that lenvatinib treatment reduced carnitine content and the expression of carnitine-related and oxidative phosphorylation (OXPHOS) proteins in the skeletal muscle of rats. Therefore, this study aimed to evaluate the effects of L-carnitine on myotoxic and anti-angiogenic actions of lenvatinib. Co-administration of L-carnitine in rats treated with lenvatinib for two weeks completely prevented the decrease in carnitine content and expression levels of carnitine-related and OXPHOS proteins, including carnitine/organic cation transporter 2, in the skeletal muscle. Moreover, L-carnitine counteracted lenvatinib-induced protein synthesis inhibition, mitochondrial dysfunction, and cell toxicity in C2C12 myocytes. In contrast, L-carnitine had no influence on either lenvatinib-induced inhibition of vascular endothelial growth factor receptor 2 phosphorylation in human umbilical vein endothelial cells or angiogenesis in endothelial tube formation and mouse aortic ring assays. These results suggest that L-carnitine supplementation could prevent lenvatinib-induced muscle toxicity without diminishing its antineoplastic activity, although further clinical studies are needed to validate these findings.